An Assessment of the agricultural arts program : a basis for staff development program - Pascua, Romualdo F. (Laoag City, Ilocos Norte : [s.n.], 2004)
The purpose of this study is to assess the extent of implementation of the elementary agricultural arts program in the public elementary schools of Dingras District I and II, Division of Ilocos Norte as a basis for program development.
Bibliography: pages 122-124.
CHED-La Union
Keywords: Agriculture -- Study and teaching